L’alternance entre le sujet nul et pronominal en roumain dans une perspective romane (Revista Cercurilor studenţeşti ale Departamentului de Limba şi Literatura Franceză, 2024)
This article focuses on the differences in the comprehension and the production of null and pronominal subjects in Romanian. It shows the importance of an empirical approach (experiments and corpus investigation) for the study of syntactic alternations, such us the null pronominal subject alternation in prodrop Romance languages, which cannot be described by the classical categorical syntactic constraints (cf. grammatical vs. agrammatical dychotomy), but rather by soft constraints, that reflect the preferences of the speakers for one structure or the other. This research allows us to observe (micro)variations within prodrop Romance languages. It also shows that an adequate analysis of such an alternation should be based on a multifactorial analysis, that takes into account factors from various linguistic levels (in particular syntax and discourse).
Keywords: null subject; pronominal subject; alternation; antecedent; Romance; empirical approach